2017
DOI: 10.1038/nm.4293
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 is a potential therapeutic target for H3K27M-mutant pediatric gliomas

Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive brain tumor that is located in the pons and primarily affects children. Nearly 80% of DIPGs harbor mutations in histone H3 genes, wherein lysine 27 is substituted with methionine (H3K27M). H3K27M has been shown to inhibit polycomb repressive complex 2 (PRC2), a multiprotein complex responsible for the methylation of H3 at lysine 27 (H3K27me), by binding to its catalytic subunit EZH2. Although DIPGs with the H3K27M mutation show global loss of H3K27me3, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
438
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(495 citation statements)
references
References 42 publications
37
438
4
Order By: Relevance
“…In diffuse midline glioma, the upregulation of transcription activity is also related to the loss of PRC2 repression function [15, 29]. As indicated by Mohammad et al [40] and Piunti et al [41], H3K27M tumor also requires PRC2-EZH2 for tumor growth preservation and proliferation [40-42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diffuse midline glioma, the upregulation of transcription activity is also related to the loss of PRC2 repression function [15, 29]. As indicated by Mohammad et al [40] and Piunti et al [41], H3K27M tumor also requires PRC2-EZH2 for tumor growth preservation and proliferation [40-42]. …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, H3K27M progresses through H3K27 acetylation and represses PRC2 activity [41, 42]. Mohammad et al [40] added the evidence that H3K27M is excluded from some loci due to DNA methylation [42]. This methylation results in the incorporation of H3K27M at the weak polycomb target, but this is not enough to reduce the overall activity of PRC2.…”
Section: Discussionmentioning
confidence: 99%
“…Given its role as a methyltransferase that targets H3K27, EZH2 is considered as a repressor of tumor suppressors such as p19, B-cell lymphoma-2-interacting protein, p57, E-cadherin, and Runt-related transcription factor 3 (38). Recent proteomic and biochemical studies have reported that EZH2 phosphorylation at S21 inhibits H3K27 trimethylation and consequently, expression of polycomb repressive complex 2 target genes (39).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicated that elevated expression of EZH2 was observed in many malignant tumors and was significantly associated with poor outcome in cancer patients [21]. Thus, pharmacological inhibition of EZH2 or agents triggering EZH2 degradation are promising therapeutic strategies for the treatment of various cancer types [22][23][24]. In studies that assess the relationship between EZH2 expression and the clinical outcomes in patients with colorectal cancer treated with anti-EGFR therapeutics, the authors showed that EZH2 expression was associated with the survival in patients with colorectal cancer who were treated with anti-EGFR therapeutics.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%